Making Connections: Integrative Signaling Mechanisms Coordinate DNA Break Repair in Chromatin - Sanchez, Anthony; Lee, Doohyung; Kim, Dae In; Miller, Kyle M. (Frontiers in Genetics, 2021)
DNA double-strand breaks (DSBs) are hazardous to genome integrity and can promote mutations and disease if not handled correctly. Cells respond to these dangers by engaging DNA damage response (DDR) pathways that are able to identify DNA breaks within chromatin leading ultimately to their repair. The recognition and repair of DSBs by the DDR is largely dependent on the ability of DNA damage sensing factors to bind to and interact with nucleic acids, nucleosomes and their modified forms to target these activities to the break site. These contacts orientate and localize factors to lesions within chromatin, allowing signaling and faithful repair of the break to occur. Coordinating these events requires the integration of several signaling and binding events. Studies are revealing an enormously complex array of interactions that contribute to DNA lesion recognition and repair including binding events on DNA, as well as RNA, RNA:DNA hybrids, nucleosomes, histone and non-histone protein post-translational modifications and protein-protein interactions. Here we examine several DDR pathways that highlight and provide prime examples of these emerging concepts. A combination of approaches including genetic, cellular and structural biology have begun to reveal new insights into the molecular interactions that govern the DDR within chromatin. While many questions remain, a clearer picture has started to emerge for how DNA-templated processes including transcription, replication and DSB repair are coordinated. Multivalent interactions with several biomolecules serve as key signals to recruit and orientate proteins at DNA lesions, which is essential to integrate signaling events and coordinate the DDR within the milieu of the nucleus where competing genome functions take place. Genome architecture, chromatin structure and phase separation have emerged as additional vital regulatory mechanisms that also influence genome integrity pathways including DSB repair. Collectively, recent advancements in the field have not only provided a deeper understanding of these fundamental processes that maintain genome integrity and cellular homeostasis but have also started to identify new strategies to target deficiencies in these pathways that are prevalent in human diseases including cancer.